Creating Dementia-Friendly Communities for Social Inclusion: A Scoping Review. (May 2021) - Hung, Lillian; Hudson, Allison; Gregorio, Mario; Jackson, Lynn; Mann, Jim; Horne, Neil; Berndt, Annette; Wallsworth, Christine; Wong, Lily; Phinney, Alison
Aims: This scoping review explores key strategies of creating inclusive dementia-friendly communities that support people with dementia and their informal caregiver.Background: Social exclusion is commonly reported by people with dementia. Dementia-friendly community has emerged as an idea with potential to contribute to cultivating social inclusion.Methods: This scoping review follows the Joanna Briggs Institute scoping review methodology and took place between April and September 2020. The review included a three-step search strategy: (1) identifying keywords from CINAHL and AgeLine; (2) conducting a second search using all identified keywords and index terms across selected databases (CINAHL, AgeLine, MEDLINE, PsycINFO, Web of Science, ProQuest, and Google); and (3) hand-searching the reference lists of all included articles and reports for additional studies.Results: Twenty-nine papers were included in the review. Content analysis identified strategies for creating dementia-friendly communities: (a) active involvement of people with dementia and caregivers (b) inclusive environmental design; (c) public education to reduce stigma and raise awareness; and (d) customized strategies informed by theory.Conclusion: This scoping review provides an overview of current evidence on strategies supporting dementia-friendly communities for social inclusion. Future efforts should apply implementation science theories to inform strategies for education, practice, policy and future research.